The Chinese Non-Equivalent Words from the Old Tea House of Old Tales and Photos of Kunming in Reminiscence and Their Ways of Translation into English - Liu, Peng (International Journal of Multidisciplinary Research, 2026)
This article puts concentration on the Chinese non-equivalent words in the Old Tea House part from the book Old Tales and Photos of Kunming in Reminiscence and the methods adopted in translating these non-equivalent words into English. By using the theoretical analysis, induction and deduction, this article displays many tables to give a classification of the non-equivalent words and the translation strategies, meanwhile, with the statistic ways, the article specifically shows the proportions of the non-equivalent words and the translation methods, so as to spread Chinese culture abroad and smoothly carry on cross cultural communication.